2022
DOI: 10.3390/cells11050878
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Intestinal Epithelial Permeability via Protease-Activated Receptor-2-Induced Autophagy

Abstract: Protease-activated receptor 2 (PAR2) alleviates intestinal inflammation by upregulating autophagy. PAR2 also modulates tight junctions through β‑arrestin signaling. Therefore, we investigated the effect of PAR2-induced autophagy on intestinal epithelial tight junctions and permeability. RT-PCR, Western blot analysis, and immunoprecipitation were performed to investigate the underlying molecular mechanisms by which PAR2 regulates autophagy and intestinal epithelial tight junctions. Inhibition of PAR2 by GB83, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Recent research found that autophagy promotes membrane localization of occluding protein, a principal TJ component involved in TJ barrier enhancement, which could protect against inflammation-induced barrier loss[ 12 ]. Furthermore, Kim et al [ 13 ] discovered that protease-activated receptor 2 regulates autophagy and intestinal epithelial TJs, thus reducing intestinal epithelial permeability. Additionally, another study discovered that rapamycin (autophagy inducer) dramatically improved intestinal damage in benzo[a]pyrene induced intestinal epithelial TJ disruption[ 14 ].…”
Section: Autophagy and Gi Physical Barrier Functionmentioning
confidence: 99%
“…Recent research found that autophagy promotes membrane localization of occluding protein, a principal TJ component involved in TJ barrier enhancement, which could protect against inflammation-induced barrier loss[ 12 ]. Furthermore, Kim et al [ 13 ] discovered that protease-activated receptor 2 regulates autophagy and intestinal epithelial TJs, thus reducing intestinal epithelial permeability. Additionally, another study discovered that rapamycin (autophagy inducer) dramatically improved intestinal damage in benzo[a]pyrene induced intestinal epithelial TJ disruption[ 14 ].…”
Section: Autophagy and Gi Physical Barrier Functionmentioning
confidence: 99%
“…OCT maintains basal levels of autophagy in Caco2 cells through SSTR2. Previous studies revealed that autophagy has an important role in maintaining the intestinal epithelial barrier by regulating TJ proteins (34,35). To determine the protective mechanisms of OCT in intestinal TJ barrier function, the formation of autophagosomes and autophagolysosomes in Caco2 cells was observed using TEM.…”
Section: Oct Prevents Lps-induced Intestinal Epithelial Cell Injury Inmentioning
confidence: 99%
“…Recently, it has been shown that, in contrast to larazotide acetate, peptidic antagonists of PAR 2 , including FSLLRY-NH 2 or SLIGRL-NH 2 , decreased the expression of ZO-1 and claudin-1 and destroyed the barrier function of nasal epithelial cells [ 121 ]. Similarly, a small molecule antagonist, GB83, exerted harmful effects on colon epithelial cells by decreasing the expression of autophagy- and TJ-related factors and increased permeability [ 234 ]. In contrast, inhibition of the PAR 2 pathway by GB88 in lung epithelial cells [ 235 ] or using I-191 in arterial endothelial cells [ 236 ] moderated actin rearrangement and TJ disruption and reduced the permeability of the cellular monolayers.…”
Section: Zonulin Pathway As a Therapeutic Targetmentioning
confidence: 99%